2005
DOI: 10.1128/aem.71.6.3153-3157.2005
|View full text |Cite
|
Sign up to set email alerts
|

First Detection and Genotyping of Human-Associated Microsporidia in Pigeons from Urban Parks

Abstract: Microsporidia are ubiquitous opportunistic parasites in nature infecting all animal phyla, and the zoonotic potential of this parasitosis is under discussion. Fecal samples from 124 pigeons from seven parks of Murcia (Spain) were analyzed. Thirty-six of them (29.0%) showed structures compatible with microsporidia spores by staining methods. The DNA isolated from 26 fecal samples (20.9%) of microsporidia-positive pigeons was amplified with specific primers for the four most frequent human microsporidia. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 57 publications
(79 reference statements)
2
86
1
Order By: Relevance
“…Is man a natural reservoir for the parasite or an accidental host in whom the infection becomes possible because of the deterioration of his immune system? For instance, after being identified in humans, spores of E. bieneusi were detected in numerous animal species, especially mammals but also birds, and in environmental source such as surface water, swimming pools or rivers (Coupe et al, 2006;Dowd et al, 1998;Fournier et al, 2000;Haro et al, 2006;Haro et al, 2005;Santin et al, 2004;Sparfel et al, 1997). Analysis of the sequence of the 243-bp internal transcribed spacer rRNA gene has revealed a considerable genetic variation within E. bieneusi isolates of human and animal origins.…”
Section: Genotypic Diversity and Host Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Is man a natural reservoir for the parasite or an accidental host in whom the infection becomes possible because of the deterioration of his immune system? For instance, after being identified in humans, spores of E. bieneusi were detected in numerous animal species, especially mammals but also birds, and in environmental source such as surface water, swimming pools or rivers (Coupe et al, 2006;Dowd et al, 1998;Fournier et al, 2000;Haro et al, 2006;Haro et al, 2005;Santin et al, 2004;Sparfel et al, 1997). Analysis of the sequence of the 243-bp internal transcribed spacer rRNA gene has revealed a considerable genetic variation within E. bieneusi isolates of human and animal origins.…”
Section: Genotypic Diversity and Host Specificitymentioning
confidence: 99%
“…While early investigation revealed that coccidian parasites were a leading cause of chronic diarrhoea in AIDS patients, the development of improved microscopic, immunological and al., 1985). The development of new tools for diagnosis and especially molecular methods have shown that E. bieneusi was present in a large number of domestic and wild mammals as well as birds (Haro et al, 2006;Haro et al, 2005;Kondova et al, 1998;and reviewed in Mathis et al, 2005). Thanks to molecular methods again, the potential of zoonotic transmission was quickly supported by phylogenetic studies showing that several genotypes can infect humans as well as animals (Curry, 1999;Dengjel et al, 2001;Drosten et al, 2005;Lobo et al, 2006a;Santin et al, 2006;Sulaiman et al, 2003a;Sulaiman et al, 2003b;Sulaiman et al, 2004).…”
mentioning
confidence: 99%
“…The most common species of pigeon in the Canary Islands is Columba livia which inhabits forests, cities and villages (Emmerson 1985). This species can transmit microorganisms to humans that could be pathogenic as is the case of Cryptococcus neoformans (Emmons 1951(Emmons , 1955Kwon-Chung and Bennett 1978) or, more recently, Enterocytozoon bieneusi and Encephalitozoon intestinalis (Haro et al 2005). On the other hand, it is known that some birds can acquire C. hominis oocysts from local garbage and other unhygienic places (Graczyk et al 2008), as it could be wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people and children are at a higher risk to come in close contact with pigeons in gardens and public parks (Haro et al 2005). The most common species of pigeon in the Canary Islands is Columba livia which inhabits forests, cities and villages (Emmerson 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Enterocytozoon bieneusi has been reported to occur in several species of domestic and wild animals, including dogs, cats, pigs, and cattle (3). Recent surveys found that pigs and park pigeons had genotypes of E. bieneusi that were potentially infectious to humans (2,10). Cattle in the United States and other countries were primarily infected with host-specific E. bieneusi but also carried some genotypes previously found in humans, and thus the infection was potentially zoonotic (17,19).…”
mentioning
confidence: 99%